Chatbot interaction development and assessment that assists teachers in inserting content into ITS MAZK - Pozzebon, Eliane; Moro, Francielli Freitas; Pereira, Vinicius Ferri; Angeloni, Maria Paula Corrêa (Seven Editora, 2023)
This paper aims to present the use of a chatbot as an alternative for teachers using an Intelli-gent Tutoring System and also verify MAZK’s chatbot acceptance among the instructors, as this functionality was developed in MAZK’s system exclusively for this purpose. A ques-tionnaire was carried out with 32 teachers, most of them beginners on MAZK. These in-structors should set up a class with the chatbot’s help and it was noticeable that this re-source’s use in their training was well accepted due to the practicality of an online tool. Still, some of the instructors had questions if they could learn all the aspects of the system only through the chatbot’s help. Teachers who had previously used MAZK considered the chat-bot’s development a necessary improvement as a supporting tool. DOI:https://doi.org/10.56238/ptoketheeducati-028